2017
DOI: 10.4236/ajcc.2017.62013
|View full text |Cite
|
Sign up to set email alerts
|

Households Vulnerability and Adaptation to Climate Variability Induced Water Stress on Downstream Kaduna River Basin

Abstract: Water stress is one of the risks emanating from worsening climatic variations. It poses serious threats on vulnerable continents, people and livelihoods globally. However, little information is available on how the specific climate threat is impacting people's livelihoods and water resources on different temporal and spatial scales in Nigeria basins. This study aimed at investigating household vulnerability and adaptation to water stress induced by climate variability on a downstream Kaduna River basin with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Yet lack of ability to follow such trainings increases the sensitivity of the smallholder farmer. This is also consistent with Chinwendu et al (2017) who found that inadequate education, access to resources , poor local institutional capacity and services, and gender were a key factors that shaped vulnerability. Mbakahya and Ndiema (2015) argued that factors such as poverty and hunger, poor health, low levels of education, gender inequality, contribute to vulnerability.…”
Section: Distribution Of Respondents By Educationsupporting
confidence: 88%
“…Yet lack of ability to follow such trainings increases the sensitivity of the smallholder farmer. This is also consistent with Chinwendu et al (2017) who found that inadequate education, access to resources , poor local institutional capacity and services, and gender were a key factors that shaped vulnerability. Mbakahya and Ndiema (2015) argued that factors such as poverty and hunger, poor health, low levels of education, gender inequality, contribute to vulnerability.…”
Section: Distribution Of Respondents By Educationsupporting
confidence: 88%
“…Supplemental information related to this paper is available at the Journals Online website: https://doi.org/10.1175/WAF-D-19-0168.s1. (i.e., high sensitivity to initial conditions) precludes skillful weather forecasts for lead times greater than two to three weeks (Buizza and Leutbecher 2015). To provide forecast information about the atmosphere a month or season ahead, methods that capture important boundary conditions (e.g., ocean processes, sea ice) are the key sources of long-term predictability.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of vulnerability assessment, scholars have adopted diverse assessment approaches and applied them at different scales. Upon reviewing the relevant literature, climate change assessments have been categorized in diverse groups, such as the "Livelihood Vulnerability Index" in the context of climate change [19,[22][23][24][25], "Social Vulnerability to Climate Change" [3,26,27], "Climate Vulnerability Index" [20,28,29], and "Household Vulnerability to Climate Change" [21,[30][31][32]. Of the vulnerability indices, the "Livelihood Vulnerability Index" has been most cited, notably considering a wide range of parameters [19,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, few scientists [30] have utilized the term "Sustainable Livelihood Framework (SLF)" in order to measure household vulnerability considering the five assets of the social, human, financial, natural and physical, and livelihood diversification aspects. The vulnerability indices found in the scholarly literature [19][20][21][22][23][24][25][26][27][28][29][30][31][32] reveal combined and individual scores of various dimensions of vulnerability at different spatial settings, which range from small communities to regions. The findings from the aforementioned vulnerability indices have contributed to developing effective adaptations for communities and regions, but vulnerable households may be left out of the adaptation planning processes.…”
Section: Introductionmentioning
confidence: 99%